CHARACTERISTICS OF PATIENTS WITH CEREBRAL STROKE OR TRANSIENT ISCHEMIC ATTACK, INCLUDED INTO THE LIS-2 REGISTER (LYUBERTSY STUDY OF MORTALITY IN PATIENTS AFTER STROKE) - S. Yu. Martsevich; N. P. Kutishenko; A. Yu. Suvorov; M. L. Ginzburg; A. D. Deev; S. A. Boytsov; A. V. Akimova; E. V. Daniels; N. A. Dmitrieva; L. Yu. Drozdova; N. Yu. Zhuravskaya; O. V. Lerman; et al. (Рациональная фармакотерапия в кардиологии)
Aim. To provide final data on the three-year period of the inclusion of patients; to give most accurate "portrait" of patients hospitalized with a brain stroke within the framework of the LIS-2 register (Lyubertsy study of mortality in patients after stroke).Material and methods. All patients (n=960) admitted to the Lyubertsy district hospital №2 with stroke for the period from 01.2009 to 12.2011 were included into the study.Results. Men accounted for 37.5%, women - 62.5%, mean age was 71.1±9.8 years. The history of hypertension was present in 833 patients (86.8%), atrial fibrillation in 252 (26.8%) patients, 199 (20.7%) patients had previously undergone stroke. In-hospital mortality was 21.6% (207 patients had died; mean age 72.9±9.8 years). Low frequency of the antihypertensive therapy (34.5%), lipid-lowering therapy (0.7%), antiplatelet agents (5.7%), anticoagulation therapy prescription in patients with atrial fibrillation was detected.Conclusion. Insufficient assignment of drugs with a proven effect on the prognosis in patients with risk factors prior to the development of the reference stroke draws attention. High incidence of recurrent strokes indicates an underactive secondary prevention.